2015
DOI: 10.4103/0019-5545.166640
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for depression among community resident older people in Kerala

Abstract: Background:Depression is the most common mental health problem in late-life. We need more information about the incidence and prevalence of major and minor syndromes of depression in older people. This will help in service development.Aims:To estimate the prevalence of depressive disorders among community resident older people in Kerala, India and to identify factors associated with late-life depression.Materials and Methods:Two hundred and twenty community resident older subjects were assessed for depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
5
18
2
Order By: Relevance
“…The survey results showed that the prevalence of depressive features in the elderly was 47.4% (45.9% in male and 48.5% in women). These results are higher than those observed in India (39.1%), 19 in Hong Kong (30.0%), 20 amongst elderly Chinese immigrants in Western countries (20.0% – 30.0%), 21 and in South Korea (26.0%), 22 as well as being lower than that of elderly Chinese (59.8%) 16 reported in previous studies. The differences may be due to a difference in sampling design, assessment tools for depressive features or objects of study.…”
Section: Discussioncontrasting
confidence: 65%
“…The survey results showed that the prevalence of depressive features in the elderly was 47.4% (45.9% in male and 48.5% in women). These results are higher than those observed in India (39.1%), 19 in Hong Kong (30.0%), 20 amongst elderly Chinese immigrants in Western countries (20.0% – 30.0%), 21 and in South Korea (26.0%), 22 as well as being lower than that of elderly Chinese (59.8%) 16 reported in previous studies. The differences may be due to a difference in sampling design, assessment tools for depressive features or objects of study.…”
Section: Discussioncontrasting
confidence: 65%
“…Depression is another common disease in older people (Nakulan, Sumesh, Kumar, Rejani, & Shaji, ). A great number of studies have shown that the prevalence of depression is a significant and common psychological health problem in older patients with hypertension (Tel, ; Testa et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 2 3 4 ] We recently reported a prevalence of 39.1% for depressive disorder in a rural community. [ 5 ] A recent review article concluded that depression is quite common in community-resident older people in India. [ 6 ] Early diagnosis of depression is important for effective intervention.…”
Section: Introductionmentioning
confidence: 99%